Hesiod's works and days : how to teach self-sufficiency - Canevaro, Lilah Grace (Oxford University Press, 2015)
Hesiod's 'Works and Days' was often performed in its entirety, but was also relentlessly excerpted, quoted, and reapplied. This volume situates the poem within these two modes of reading and argues that the text itself, through Hesiod's complex mechanism of rendering elements detachable whilst tethering them to their context for the purposes of the poem, sustains both treatments